2008
DOI: 10.1007/s12039-008-0068-2
|View full text |Cite
|
Sign up to set email alerts
|

Ir/Sn dual-reagent catalysis towards highly selective alkylation of arenes and heteroarenes with benzyl alcohols

Abstract: A catalytic combination of [Ir(COD)Cl] 2 -SnCl 4 efficiently promotes the reactions of arenes and heteroarenes with 1°/2°/3° benzyl alcohols as the alkylating agents to afford the corresponding diarylmethane and triarylmethane derivatives in high yields. The scope and limitation of the reaction with respect to catalyst and substrates variation has been studied in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 79 publications
1
7
0
Order By: Relevance
“…Since product B 2-methyldiphenylmethane (electrophilic substitution product) is more thermodynamically stable and kinetically favorable, this material was observed as the major product. The rate constant for the reaction was calculated to be 2.91, which is quite good as compared to the previously reported literature and considering that our synthesized catalyst procedures are straightforward and economical. ,, Previously, in the case of iridium- and scandium-based metal–organic framework (MOF), a greater TON has been reported compared to this work (TON = 115). Iridium 42 -based different MOFs give TONs of 530 [{IrCp*Cl2}­2/AgOTf] and 950 [{IrCp*­(Otf)­2}­2/1,3-di- n -butyl-imida-zolylidene, {IrCp*­(OTf)­2}­2/1,3-di- n -methyl-4 methyl imidazole, and {IrCp*­(OTf)­2}­2/1,2-di- n -methyl imidazole], whereas scandium 11 -based MOF gives a TON of 490 {Sc­(OSO2C8F17)­3}.…”
Section: Discussionsupporting
confidence: 78%
“…Since product B 2-methyldiphenylmethane (electrophilic substitution product) is more thermodynamically stable and kinetically favorable, this material was observed as the major product. The rate constant for the reaction was calculated to be 2.91, which is quite good as compared to the previously reported literature and considering that our synthesized catalyst procedures are straightforward and economical. ,, Previously, in the case of iridium- and scandium-based metal–organic framework (MOF), a greater TON has been reported compared to this work (TON = 115). Iridium 42 -based different MOFs give TONs of 530 [{IrCp*Cl2}­2/AgOTf] and 950 [{IrCp*­(Otf)­2}­2/1,3-di- n -butyl-imida-zolylidene, {IrCp*­(OTf)­2}­2/1,3-di- n -methyl-4 methyl imidazole, and {IrCp*­(OTf)­2}­2/1,2-di- n -methyl imidazole], whereas scandium 11 -based MOF gives a TON of 490 {Sc­(OSO2C8F17)­3}.…”
Section: Discussionsupporting
confidence: 78%
“…(48) for the benzylations of the benzylic alcohols having bhydrogens for the preparation of diarylmethanes (Scheme 76). 102,103 The hard main group metal center of the complex activated the hard donor atom while the so transition metal center activated the so donor center such as the p-electron cloud. The authors observed that at room temperature the reaction was sluggish and much of the starting material remains unreacted.…”
Section: Hiyama Couplingmentioning
confidence: 99%
“…White solid (mixture from EtOH); Yield 68%; mp 58-64 °C (Lit [38], for 20, mp 85-86 °C; for 21, mp 78 °C); NMR (CDCl 3 ) δ 7.7-7.0 (m, 28H), 4.45 (s, 4H), 3.90 (s, 4H); the latter peaks in a 3:1 ratio; (Lit [39], (for 20) NMR (CDCl 3 ) δ 7.30 (m, 4H), 7.23 (m, 6H), 7.16 (m, 4H), 3.99 (s, 4H); GC also showed two peaks in a ratio of 3:1. The major isomer (20) agreed by comparison with an authentic sample as prepared below.…”
Section: 4-dibenzylbenzene (20) and 12-dibenzylbenzene (21)mentioning
confidence: 79%
“…4 [10], rare earth (III) (OSO 2 C 8 F 17 ) 3 [14] zeolites [15][16][17], [19,20], 12-tungstophosphoric acid [21], I 2 [22] IrCp* complexes [23], MoO 6 [24], NaHSO 4 /SiO 2 [25], Ph 3 P(OTf) 2 [26], Fe(III)-porphyrin [27] BF 3 -H 2 O [28], Hf 0.5 [TEAPS] PW 12 O 40 [29], choline chloride-(TfOH) 2 [30], and B(C 6 F 5 ) 3 [31]. Our method is eco-friendly as the only by-product is water and the TFA can be recycled.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation